Role of sludge retention time in mitigation of nitrous oxide emission from a pilot-scale oxidation ditch - Nan Zhou; Dang, Chenyuan; Zhirong Zhao; Shishi He; Zheng, Maosheng; Liu, Wen; Xiangke Wang (Bioresource Technology, 2019)
Nitrous oxide (N2O) emission from wastewater treatment plants (WWTPs) has become a focus of attention due to its significant greenhouse effect. In this study, the role of sludge retention time (SRT) in mitigation of N2O emission from a pilot-scale oxidation ditch was systematically investigated. The activated sludge system that operated at SRT of 25 days demonstrated significantly lower N2O emission factor, higher resistance to ammonia overload and aeration failure shock than those obtained at SRT of 15 days no matter which hydraulic retention time (HRT) was adopted. Batch experiments revealed that nitrifier denitrification (ND) was the primary mechanism of N2O generation. However, more microbes affiliated with Nitrospira genera were harbored in the system at SRT 25 d, which could effectively avoid nitrite accumulation, a key factor promoting N2O generation by ND. PICRUSt results further suggested the system at SRT 25 d possessed higher genetic potential for N2O reduction reflected by the more abundant nitrous-oxide reductase.
Keywords: Ammonia overload shock; Hydraulic retention time; Nitrous oxide; Oxidation ditch; Sludge retention time